Effect of different motor skills training on motor control network in the frontal lobe and basal ganglia - Shi, Jilong; Wang, Jun; Lang, Jian; Zhang, Zhuo; Bi, Yan; Liu, Ran; Jiang, Shan; Hou, Lijuan (Biology of Sport, 2020)
ABSTRACT: During human motor control, the three pathways of motor control coordinate to complete human response and inhibition control, so whether different types of motor skills training will affect the three pathways of motor control is the main question in this study. Magnetic resonance imaging was combined with behavioural evaluation to analyse the effects of different special training sessions on the motor control network of the frontal lobe and basal ganglia and to explore the role of the central nervous system in the regulation of motor behaviour. A Stop-signal paradigm was used to measure reaction and inhibition capacity, functional magnetic resonance imaging was used for whole brain scanning, and resting state data were collected. Compared to the control group, the competitive aerobics athletes had better reflexes while the soccer players had both better reflexes and inhibitory control. Furthermore, we found that training in the two sets of skills resulted in significant differences in different resting state brain function parameters compared with the control group. Additionally, there were significant differences among the three groups in the direct and indirect pathways of motor control in terms of functional connectivity. Open skill training may improve reaction ability while closed skill training improve both reaction and inhibition ability. These results suggest that the strength of the functional connectivity between the right inferior frontal gyrus and the left putamen may be a key to improving the inhibitory, and the left supplementary motor area- bilateral thalamic loop may play an inhibitory role in motor control.